1991
DOI: 10.1007/bf00010426
|View full text |Cite
|
Sign up to set email alerts
|

Growth and uptake of N, P, K and B by Pinus radiata D. Don in response to applications of borax

Abstract: Leader dieback associated with B deficiency in P. radiata D. Don plantations was treated with borax applied at rates of 50, 100 and 150 kg ha -1. This initially increased B in foliage from 5 to 40, 80 and 110/xg g-~ respectively, and was followed by a rapid decline and stabilisation at around 25/xg g-I for the duration of the study. Annual fluctuations in foliage B levels were strongly correlated with rainfall during the preceding spring and summer. Uptake of N, P and K increased as a result of applied B and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 15 publications
2
35
0
Order By: Relevance
“…Boron deficiency is known to lessen shoot height growth in many coniferous species (Hopmans and Flinn 1984;Veijalainen et al 1984;Stone 1990;Hopmans and Clerehan 1991). Measurement of the height of B-deficient trees is somewhat questionable, however, as those trees usually have multileadered crowns due to the effects of the condition on apical dominance.…”
Section: Introductionmentioning
confidence: 97%
“…Boron deficiency is known to lessen shoot height growth in many coniferous species (Hopmans and Flinn 1984;Veijalainen et al 1984;Stone 1990;Hopmans and Clerehan 1991). Measurement of the height of B-deficient trees is somewhat questionable, however, as those trees usually have multileadered crowns due to the effects of the condition on apical dominance.…”
Section: Introductionmentioning
confidence: 97%
“…Hopmans and Clerehan (1991) found that the B concentrations in Pinus radiata were highest in the old needles in trees with little boron (4±7 mg kg À1 ), but in B-fertilized trees, the concentrations were highest in the current needles. Based on their results, Hopmans and Clerehan (1991) postulated that there was internal redistribution of boron in Pinus radiata trees. According to Ziegler (1975), sucrose is the only carbohydrate translocated in the phloem of Norway spruce.…”
Section: Introductionmentioning
confidence: 97%
“…Consistent with Dugger's (1983) ideas Wikner (1983) suggested that B was not mobile in Norway spruce. In contrast, it has been suggested that B is mobile in Scots pine (Helmisaari 1990b, Wikner 1983 and Monterey pine (Hopmans and Clerehan 1991). In this section we reassess published data for these species, and present previously unpublished data for lodgepole pine.…”
Section: Evidence From the Forestmentioning
confidence: 81%
“…In Monterey pine (Pinus radiata) Hopmans and Clerehan (1991) found that B concentrations were slightly higher in older needles than in current year needles of trees with little boron (4-7 mg kg -1 ) (r = 0.79, P = 0.42), but in B-fertilized trees, the concentrations were lower in older needles than in current needles (r = -0.99, P = 0.008, Fig. 5).…”
Section: Monterey Pinementioning
confidence: 97%
See 1 more Smart Citation